Improvement in Fitted Filtration Efficiency of N95 Respirators With Escalating Instruction of the Wearer - Hao Chen, PhD; Edward R. Pennington, PhD; Martin W. Case, BS; Haiyan Tong, MD, PhD; Ana G. Rappold, PhD; James M. Samet, PhD, MPH; Steven E. Prince, PhD (Elsevier, 2022)
Introduction: Fitted filtration performance of an N95 respirator may benefit from differing levels of instructions. Methods: Using a modified Occupational Safety and Health Administration fit test protocol, we measured fitted filtration efficiency for an N95 respirator in 21 screened, healthy participants given 4 levels of escalating instruction: (1) uninstructed (baseline), (2) written/pictorial manufacturer instructions, (3) step-by-step video demonstration, and (4) staff instruction (visual inspection of respirator fit and verbal suggestions to adjust when applicable). Results: Baseline fitted filtration efficiency was not significantly different between participants with or without previous experience of N95 use. Clear improvements in fitted filtration efficiency were observed progressing from baseline (average=86.1%) to manufacturer paper instructions (93.3%), video instructions (97.5%), and post staff intervention (98.3%). Baseline fitted filtration efficiency values were significantly lower than those after video instruction (p<0.037) and staff intervention (p<0.033) sessions. Conclusions: Beyond uninstructed wear or provision of manufacturer instructions, efforts to train and instruct users in proper respirator fit principles with visual feedback are likely to yield benefits to public health outcomes in reducing respiratory exposure during air quality emergencies such as airborne viral outbreaks and wildland fires.